Grazers and predators mediate the post-settlement bottleneck in Caribbean octocoral forests - Wells, Christopher D.; Benz, Joseph; Tonra, Kaitlyn J.; Anderson, Emily R.; Lasker, Howard R. (Frontiers in Marine Science, 2024)
In the Caribbean, reef-building scleractinian corals have declined precipitously and octocorals have emerged as one of their main successors. The success of octocorals and the formation of octocoral forests has been attributed to their continuing recruitment to reef habitats. Benthic grazers on coral reefs can facilitate the growth and recruitment of corals by reducing the abundance of competitive algal turfs and macroalgae, but grazing can also hinder corals through sublethal damage to coral tissue and predation of recruits. We assessed the effects of grazing by fishes and the sea urchin Diadema antillarum as well as predation by mesofauna on octocoral recruits in a series of manipulative in situ and ex situ experiments. Exposure to fish and urchin grazing significantly reduced recruitment and survival of single-polyp octocorals, while turf associated mesofauna did not significantly affect recruitment or survival. We also found a positive relationship between octocoral recruitment and the abundance of turf algae, which may reflect the deleterious effect of grazing on turf algae as well as its effects on recruits. These data suggest that grazers and predators mediate the mortality bottleneck characteristic of recruitment. Thus, the declines in the abundance of grazing fishes and urchins throughout the Caribbean may have contributed to the increase in abundance of octocorals in the Caribbean, concurrent with the loss of scleractinians.